ОТНОШЕНИЕ ЧЕЛОВЕКА К ОКРУЖАЮЩЕЙ СРЕДЕ В ВОЗЗРЕНИЯХ ПРАВОСЛАВИЯ - Полуянов, В. П. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 1970)
Рассматриваются проблемы отношения человека к окружающей природной среде,религиозно-нравственные основы мира и главные причины экологического кризиса. Анализируютсяпричины обострения противоречий в системе «общество–природа», а также высказываниеРусской православной Церкви о полном преодолении экономического кризиса в условиях кризисадуховного.В.П. ПолуяновВІДНОШЕННЯ ЛЮДИНИ ДО НАВКОЛИШНЬОГО СЕРЕДОВИЩА У ПОГЛЯДАХПРАВОСЛАВ'ЯРозглядаються проблеми відношення людини до природного довкілля, релігійно–етичніоснови світу і головні причини екологічної кризи. Аналізуються причини загострення протиріч всистемі «суспільство–природа», а також вислів Російській православній Церкві про повнеподолання економічної кризи в умовах кризи духовного.Ключові слова: екологія, православ'я, довкілля, духовність, криза, людина.V. PoluyanovTHE RELATION OF THE PERSON TO ENVIRONMENT IN ORTHODOXY VIEWSProblems of the relation of the person to a surrounding environment, religious–moral bases ofthe world and the main reasons of ecological crisis are considered. The reasons of an aggravation ofcontradictions in system "society–nature", and also the statement of Russian orthodox Church about fullovercoming of an economic crisis in the conditions of crisis spiritual are analyzed.Keywords: ecology, Orthodoxy, environment, spirituality, crisis, the person.